Effect of kerosene combustion gases on the pulmonary tissue in mice - Al-Omar, Muthanna A.; Al-Zamily, Adil H. (The Iraqi Journal of Veterinary Medicine, 2001)
This study aims to throw light on the harmful effect of kerosene combustion on the respiratory system in mice. Experimental animals were exposed to combustion gases of kerosene for 2, 4 and 6 hours/day for 5 days a week. Exposure was lasted for 8 consecutive weeks. Histopathological changes were examined in trachea and lung tissues. Results showed different stages of tissue damages were emphysema was the most severe. Filtration of lymphocytes was also remarkable accompanied by increase in alveolar macrophages. There was evident and direst correlation between exposure time and the severity of effects.